A preliminary study of diffusion tensor imaging in root entry zone of primary trigeminal neuralgia - Wang, Yiwen; Wang, Danni; Wu, Yingwei; Zhu, Ce; Wei, Wenbin; Li, Yao; Li, Lingzhi; Chen, Wantao; Chen, Minjie (Frontiers in Neuroanatomy, 2023)
Objective Primary Trigeminal Neuralgia (PTN) is a common and refractory neurological disease. Conventional vascular compression theory could not completely explain the etiology and pathogenesis of PTN. This study used diffusion tensor imaging (DTI) to demonstrate the microstructural changes of root entry zone (REZ) region in PTN patients. Materials and methods DTI sequences was performed on PTN patients and healthy controls (HCs). Clinical data included affected side, disease course and visual analogue scale (VAS) were collected. Quantitative DTI variables such as FA, MD, AD and RD of the root entry/Exit zone (REZ) were measured and compared in PTN/HCs, affected/unaffected side, and pre/post operation groups. The PCoA was established to conduct overall differences between PTN group and the HCs. Results A total of 17 patients with PTN (mean age 59.29 ± 8.53; 5 men) and 34 HCs (mean age 57.70 ± 6.37; 10 men) were included. Lower FA value of the affected side of PTN group was observed compared to the unaffected side and the HCs (p = 0.001), whereas the values of MD, AD and RD were significantly increased (p < 0.001). Moreover, the decrease of FA value was recovered post operation. PCoA results of the comprehensive indexes can significantly distinguish PTN group from HCs (r = 0.500, p < 0.001). Conclusion Quantitative variables derived from DTI in REZ had significantly different profiles between PTN patients and HCs, which were associated with VAS situation and the disease course of PTN. The comprehensive index established on DTI variables were of great potential to reveal the microstructure changes in PTN patients and predict the therapeutic effect.